2021
DOI: 10.1002/pmh.1520
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophizing, negative affectivity, and borderline personality disorder

Abstract: The core features of borderline personality disorder (BPD) include problematic interpersonal relationships, behavioral and affective dysregulation, identity problems, and cognitive dysregulation. Cognitive dysregulation, such as catastrophizing, rumination, and thought suppression, contributes to emotion dysregulation in BPD. Previous research suggested that thought suppression fully mediated the relationship between negative affect intensity/reactivity and BPD symptoms. We predicted that catastrophizing simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 42 publications
0
1
1
Order By: Relevance
“…For the current study, we used seven of the nine subscales (excluding self-blame and other-blame) that we hypothesized to change after participating in the mindfulness intervention. Although prior research has demonstrated relatively strong internal consistency among the CERQ-SF subscales, with Cronbach's alpha ranging from 0.61 to 0.90 [85][86][87], several subscales demonstrated poor reliability (e.g., Cronbach's alpha = 0.50 for acceptance, 0.47 for rumination, and 0.54 for putting into perspective) in our sample. To remedy this and examine if there were broader patterns of coping within our sample, an oblimin-rotated principal components analysis (PCA) was computed using the seven subscales, and resulting factor scores were used in our subsequent analyses.…”
Section: Mindfulness-informed Interventioncontrasting
confidence: 76%
“…For the current study, we used seven of the nine subscales (excluding self-blame and other-blame) that we hypothesized to change after participating in the mindfulness intervention. Although prior research has demonstrated relatively strong internal consistency among the CERQ-SF subscales, with Cronbach's alpha ranging from 0.61 to 0.90 [85][86][87], several subscales demonstrated poor reliability (e.g., Cronbach's alpha = 0.50 for acceptance, 0.47 for rumination, and 0.54 for putting into perspective) in our sample. To remedy this and examine if there were broader patterns of coping within our sample, an oblimin-rotated principal components analysis (PCA) was computed using the seven subscales, and resulting factor scores were used in our subsequent analyses.…”
Section: Mindfulness-informed Interventioncontrasting
confidence: 76%
“…Offering partial course credit as compensation for participation in educational research experiences is common for university student participants (e.g. Crosby and Witte 2023 ; MacKay and DeCicco 2020 ; Mason and Mullins-Sweatt 2021 ). As approved by the Research Ethics Boards at the five participating university sites, we provided credit points towards a final grade in a participating course as compensation for the time and effort students invested in completing the survey.…”
Section: Methodsmentioning
confidence: 99%